The Integration of Sister Village Functions in Mount Merapi Disaster Management during the COVID-19 Pandemic - Widati Widati; Aulia Widya Sakina; Anastasia Adiwirahayu (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2021)
This article examines the integration of the sister village program in the emergency response to the Mount Merapi disaster during the COVID-19 pandemic using the analysis of the AGIL functions- Adaptation (A), Goal attainment (G), Integration (I), and Latency (L). This study uses a descriptive narrative method. Primary and secondary data were collected through interviews, observations, documentation and FGDs in order to support and strengthen the results. The study findings show that according to the functionalism perspective, the condition of Nggargomulyo Village and Tamanagung Village people which are bound by the MoU sister village still has not shown harmonization. The community involvement of Tamanagung Village actively in the management of the evacuation is relatively low. Whereas community involvement in the sister village program is the basic principle of achieving the goals of this village fraternity cooperation. This condition resulted in the people of Ngargomulyo Village finding its difficult to adapt to the new refugee situation during the COVID-19 pandemic. This affects the program integration process and the functioning of the system, both internally and externally, because the program has not yet been institutionalized within the community. For this reason, it is necessary to refresh the role and function of the sister village as the main instrument in overseeing the disaster management system in Magelang Regency related to being integrative and sustainable.